ANALISIS FAKTOR- FAKTOR YANG MEMPENGARUHI LOYALITAS KONSUMEN KULINER LALAPAN BELUT SAWAH MAS GEMBUL MADIUN - Apriyanti . (STIE Pelita Nusantara Semarang, 2016)
The aim of research is for knowing which factors influence the customer’s loyalty of Lalapan Belut Sawah Mas Gembul In Madiun and for knowing which factor being dominant in influencing the customer’s loyalty of Lalapan Belut Sawah Mas Gembul in Madiun. This research used the nonprobability sampling, by using the criteria that customer ever bought the product the restaurant twice or more, then the technic used accidental sampling and used questionnaire such as the data resourse of the collecting date process. The questionnaire got from 100 respondents of Lalapan Belut Sawah Mas Gembul in Madiun. The result of questionnaire analysed by using factor analysis method in software SPSS 17.0. Included 21 questions. And it’s result got 6 factors which influence of customer loyalty of Lalapan Belut Sawah Mas Gembul in Madiun, such as 1). Service quality, 2). Reachable price, 3). Tangible and customer satisfaction, 4). The cleaness, 5). Product quality ,6). Price. And the dominant factor in this research is service quality by variance 40,342%. The presentasion of comulatif variance about 70,328 which these result be able to explain the factors which influence the customer’s loyalty and another ones influenced by another factors.